THE IMPACT OF INFORMATION SHARING ON SOCIAL MEDIA ON GENERATION Z'S INTENTION TO BUY GREEN GOODS - Enny Lastuti; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
The rapid growth of social media has transformed the way consumers access and share information, particularly among Generation Z, a cohort known for its strong digital engagement and environmental awareness. This study examines the impact of information sharing on social media on Generation Z’s intention to purchase green goods. Drawing on a quantitative research approach, the study analyzes key factors such as information sharing behavior, trust, environmental awareness, and social media engagement. The findings indicate that both the frequency and quality of shared content significantly influence green purchase intention, with peer-to-peer interactions playing a critical role. Environmental awareness and trust are identified as key mediating factors that strengthen the relationship between information sharing and behavioral intention. Additionally, social media engagement, including interactions with influencers and online communities, enhances the effectiveness of sustainability messages. The study also highlights both direct and indirect pathways through which social media influences purchasing behavior. These insights suggest that social media is a powerful tool for promoting sustainable consumption among Generation Z. The study contributes to the literature on digital marketing and sustainability by providing an integrated framework of social media influence. It concludes that strategic use of social media can effectively drive green purchasing behavior.